Assessing the Financial Value of Human Resource Management Programs and Employee Behaviors: A Critical Tool Still Coming of Age - Aharon Tziner; Assa Birati (Amfiteatru Economic)
This paper highlights investigations into several aspects of the field of economic assessment of human resource management strategies and worker organizational behaviors, both classic and recent. We present the reader with both an historical overview and a review of conceptual and practical developments in this field. It is important to emphasize the influence of the early studies since later financial assessment models were built on the earlier paradigms. The basic thrust of this effort is to encourage the greater employment by managers of quantitative models that allow decision makers to generate all the factors needed to estimate real financial gains and/or losses before any intervention strategy is implemented in the workplace. As indicated, the use of these quantitative models to estimate the net financial gains of using particular intervention strategies or the value of certain types of worker behaviors, can ultimately save companies from making gross tactical errors and, more positively, can assist management in promoting the organization’s long-term economic goals with all the incumbent rewards.